2018
DOI: 10.3897/phytokeys.111.28081
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and taxonomic synopsis of Poa subgenus Pseudopoa (including Eremopoa and Lindbergella) (Poaceae, Poeae, Poinae)

Abstract: Eremopoa is a small genus of annual grasses distributed from Egypt to western China. Phylogenetic analyses of plastid and nuclear ribosomal DNA show that Eremopoa species, together with the monotypic genus Lindbergella and a single species of Poa (P.speluncarum), are nested within the genus Poa, in a clade that we accept as Poasubg.Pseudopoa. Here we accept seven species, four subspecies and four varieties in Poasubg.Pseudopoa. Five new combinations are made: Poaattalica, P.diaphora var. alpina, P.diaphora var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 26 publications
3
34
0
1
Order By: Relevance
“…Our results corroborate monophyly of Poa encompassing P. apiculata Refulio (type of Tovarochloa T.D. The plastid and nrDNA trees were widely congruent and showed sister relations of P. alpina and P. bulbosa, of P. annua and P. cyrenaica, of P. diaphora and P. persica, respectively, and the latter two species together with P. sintenisii (corresponding to Poa clade E in Gillespie & al., 2018) as sister to the remaining species of Poa included in our study (Figs. 4,5).…”
Section: Circumscription Of Lineages or Generasupporting
confidence: 84%
“…Our results corroborate monophyly of Poa encompassing P. apiculata Refulio (type of Tovarochloa T.D. The plastid and nrDNA trees were widely congruent and showed sister relations of P. alpina and P. bulbosa, of P. annua and P. cyrenaica, of P. diaphora and P. persica, respectively, and the latter two species together with P. sintenisii (corresponding to Poa clade E in Gillespie & al., 2018) as sister to the remaining species of Poa included in our study (Figs. 4,5).…”
Section: Circumscription Of Lineages or Generasupporting
confidence: 84%
“…Some subsets of the genera placed here have sometimes been accepted in traditional classifications (Tzvelev, , ; Davis, ), or implied by generic arrangements (Tutin, ; Clayton & Renvoize, ). However, these subtribes were not banded together until recent molecular studies verified their relationships (Döring et al, ; Gillespie et al, , , unpublished data; Döring, ; Schneider et al, ; Soreng et al, ). They share glabrous caryopses, usually with lipid, and a short hilum (mostly less than ¼ the length), and a hairy callus in genera with more than one floret per spikelet.…”
Section: Discussionmentioning
confidence: 99%
“…is hexaploid (2n = 42) [44,50,53,54]. After Eremopoa was described, most authors accepted the genus [17,41,47,55,56], however, a comparison of chloroplast trnT-trnL-trnF and nuclear ITS-sequences showed that Eremopoa lies among Poa species on the phylogenetic tree [21,22,[57][58][59][60][61]. To date, P. diaphora has been joined with the species of genus Lindbergia Lehm.…”
Section: Discussionmentioning
confidence: 99%